Studies of molecular structure, hydrogen bonding and chemical activity of a nitrofurantoin-l-proline cocrystal: a combined spectroscopic and quantum chemical approach. Issue 78 (4th August 2016) - Pandey, Jaya; Prajapati, Preeti; Shimpi, Manishkumar R.; Tandon, Poonam; Velaga, Sitaram P.; Srivastava, Anubha; Sinha, Kirti
Abstract : Nitrofurantoin (NTF) as an API andl -proline (LP) as a co-former being used as components to form a model of cocrystal NTF-LP to predict its crystal structure. Abstract : Nitrofurantoin (NTF) has been used as an antibacterial drug to treat bacterial infections of the urinary tract. The purpose of this work is to predict the hydrogen bonds (potential synthons) present in the cocrystal of nitrofurantoin-l -proline (NTF-LP) through a computational approach (DFT calculations) and validate using vibrational spectroscopic studies. The present study illustrates the formation and characterization of the cocrystal of NTF-LP. The molecular structure of the NTF-LP cocrystal has been predicted by forming several models on the basis of the hydrogen bonding patterns observed in other NTF cocrystals. A conformational study and potential energy surface scan have been plotted around three flexible bonds of the cocrystal molecule and two stable conformers have been obtained. NBO analysis of the second order perturbation theory of the Fock matrix suggests that interaction n1 O(39) → σ*(N13–H21) is responsible for the stabilization of the molecule. Quantum theory of atoms in molecules (QTAIM) explains that all interactions are medium and partially covalent in nature as ∇ 2 ρ BCP > 0, H BCP < 0. The molecular electrostatic potential surface (MEPS) of the cocrystal has been visualized for its most electropositive potential in the region of the NH2 + group and most electronegative potential in the vicinity of the COO − group. The HOMO and LUMO energies and electronic charge transfer (ECT) confirms that charge flows from the co-former (LP) to NTF (API). Local reactivity descriptor parameters have been used to predict the reactive sites of the cocrystal and global reactivity descriptor parameters suggest that the cocrystal is softer thus more reactive in comparison to NTF. The experimental and theoretical results support the formation of the cocrystal through the strong hydrogen bond present between the NH group of NTF and carboxylate COO − group of LP and shows that LP is present in the zwitterionic form.